Geology and structural evolution in the Bheri river region, southwest Nepal - Kansakar, D. R. (Journal of Nepal Geological Society, 1991)
The rocks of the Lesser Himalaya in the Bheri River region have been divided into five stratigraphic groups. The meso-grade metamorphic rocks of the Chaurjhari Group is the oldest rock group in the area and is occurring as a klippen in the north. The Kunchha Group and the Nawakot Group are the incipiently metamorphosed sedimentary rocks while the Gondwana Group and Daban Group rocks are generally unmetamorphosed sedimentary sequences.In the frontal part of the thrust-fold belt of the Himalaya, leading imbricate fan structure is developed in the rocks of Daban Group with the Main Boundary Thrust (MBT) as the sole thrust, and the Kumak Thrust as the roof thrust. In the region further north, a complex of hinterland dipping duplex structure is envisioned between the Kumak Thrust (main sole thrust) and the Chaurjhari Thrust (main roof thrust) with a number of intermittent thrust-faults which acted as roof thrust to the underlying duplex and as sole thrust to the overlying duplex. The major planes of detachment for the generation of duplex are postulated along the incompetent basal rock members of the Nawakot Group, the Kunchha Group and the Chaurjhari Group respectively. As against the view of some of the earlier workers, a "piggy-back" sequence of thrust from higher to lower (hinterland towards the foreland) is proposed.